Rediscovery and a new locality of Carlowrightia fuertensis (Acanthaceae) after 115 years - Millán-Otero, Manuel Guillermo; Resendez-Tapia, José Jesús; González-Gallegos, Jesus Guadalupe; González-Martínez, Oscar Carlos; Pío-León, Juan Fernando (Phytotaxa, 2025)
Carlowrigthia fuertensis was known only from type material collected by J.N. Rose in 1910 in the vicinity of El Fuerte, Sinaloa, Mexico; however, these populations have not been located again. In this paper, we report a new population identified thanks to a photographic record in 2023 in the citizen science platform iNaturalist. The new population was located 300 km southeast of the original collection and is currently the only known living population, but its habitat is severely fragmented. Carlowrigthia fuertensis is easily distinguished from other species of the genus by its shrubby habit and morphology of the corolla, fruits and seeds. We present the first in situ and color photographs of the species, a distribution map with historical and current collections, as well as a proposed conservation status.